Gelatin-apatite bone mimetic co-precipitates incorporated within biopolymer matrix to improve mechanical and biological properties useful for hard tissue repair. (2013) - Won, Jong-Eun; El-Fiqi, Ahmed; Jegal, Seung-Hwan; Han, Cheol-Min; Lee, Eun-Jung; Knowles, Jonathan C; Kim, Hae-Won
Synthetic biopolymers are commonly used for the repair and regeneration of damaged tissues. Specifically targeting bone, the composite approach of utilizing inorganic components is considered promising in terms of improving mechanical and biological properties. We developed gelatin-apatite co-precipitates which mimic the native bone matrix composition within poly(lactide- co -caprolactone) (PLCL). Ionic reaction of calcium and phosphate with gelatin molecules enabled the co-precipitate formation of gelatin-apatite nanocrystals at varying ratios. The gelatin-apatite precipitates formed were carbonated apatite in nature, and were homogeneously distributed within the gelatin matrix. The incorporation of gelatin-apatite significantly improved the mechanical properties, including tensile strength, elastic modulus and elongation at break, and the improvement was more pronounced as the apatite content increased. Of note, the tensile strength increased to as high as 45 MPa (a four-fold increase vs. PLCL), the elastic modulus was increased up to 1500 MPa (a five-fold increase vs. PLCL), and the elongation rate was ∼240% (twice vs. PLCL). These results support the strengthening role of the gelatin-apatite precipitates within PLCL. The gelatin-apatite addition considerably enhanced the water affinity and the acellular mineral-forming ability in vitro in simulated body fluid; moreover, it stimulated cell proliferation and osteogenic differentiation. Taken together, the GAp-PLCL nanocomposite composition is considered to have excellent mechanical and biological properties, which hold great potential for use as bone regenerative matrices.